Government interventions in foodgrain markets : procurement and public distribution of foodgrains in India - George, P. S. (Ahmedabad : Centre for Management in Agriculture, Indian Institute of Management, 1983)
The study throws light on on a wide variety of policies adopted the Indian Government since Second world war.
Includes bibliographical references: p. 234-240.
kjo 16/01/2019
Loans
Keywords: Grain trade; Food security; Agriculture; India